Be a champion for your athlete`s health - Grindem, H.; Myklebust, G. (Journal of Orthopaedic & Sports Physical Therapy, 2020)
Many athletes push themselves beyond their limits and sacrifice short-term well-being and long-term health for a chance at victory. Elite sport shapes a certain type of character: mentally and physically tough, and unrelenting in the pursuit of the marginal gains that separate champions from the second best. The difficult question, especially for elite sports, is: How do managers, coaches, athletes, and members of the health team find the balance between protecting the athlete`s health and pursuing athletic greatness? In this viewpoint, we offer 4 perspectives on the role and responsibilities of sports physical therapists: 1. our duty of care and ethical obligations to the elite athlete; 2. how to make decisions that are in the athlete`s best interest; 3. how to build a working relationship with the athlete; 4. how to support athletes who face end of career decisions.